There Is More to the Taxonomy of Schoenus apogon (Cyperaceae) Than Meets the Eye: An Unresolved Complex With Cytological Diversity - Yu Ito; Norio Tanaka; Jeremy J. Bruhl; Karen L. Wilson; Okihito Yano (New Zealand Journal of Botany, 2026)
Schoenus apogon s . lat . is widely distributed in Australia, Japan and New Zealand. There has been limited cytological and molecular study of this species complex and putatively related species. Different chromosome numbers have been reported from New Zealand (2 n = 8) and Japan (2 n = 18), perhaps indicating taxonomic differences. We investigate the chromosome diversity and phylogenetic relationships in the S . apogon complex by root‐tip squashes to expand the sample of chromosome numbers, and by examining chloroplast and nuclear DNA gene regions ( trn L ‐trn F and ITS). Occurrence of 2 n = 8 is now known from Japan and Australia as well as New Zealand. Novel chromosome numbers recorded for Japanese samples, 2 n = 16 and 17, making an aneuploid series, and 2 n = 10 and 20 for Australian species indicate independent polypoid events. There is some evidence that the plesiomorphic chromosome number for the complex is 2 n = 10. Both gene regions recovered the S. apogon complex as monophyletic but relationships within the complex were largely unresolved. We found no support for recognition of S. caespitans and S. yarrabensis or several putative species as distinct from S. apogon . We suggest approaches for testing these results, aiming at a robust estimate of phylogeny for the complex.